2021
DOI: 10.1007/jhep11(2021)128
|View full text |Cite
|
Sign up to set email alerts
|

Removing tadpoles in a soliton sector

Abstract: It has long been known that perturbative calculations can be performed in a soliton sector of a quantum field theory by using a soliton Hamiltonian, which is constructed from the defining Hamiltonian by shifting the field by the classical soliton solution. It is also known that even if tadpoles are eliminated in the vacuum sector, they remain in the soliton sector. In this note we show, in the case of quantum kinks at two loops, that the soliton sector tadpoles may be removed by adding certain quantum correcti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…(3.17) of Ref. [39]. If one instead interprets both terms as a quantum correction to f (x) in D f , then the corresponding γ 01 0 would vanish.…”
Section: Discussionmentioning
confidence: 96%
“…(3.17) of Ref. [39]. If one instead interprets both terms as a quantum correction to f (x) in D f , then the corresponding γ 01 0 would vanish.…”
Section: Discussionmentioning
confidence: 96%
“…In ref. [22] we showed that such tadpoles can be removed by a quantum correction to the classical kink solution appearing in the displacement function D f , chosen so as to include a linear term in the Hamiltonian which exactly cancels the tadpole diagram. We saw that such a change of prescription does not affect the quantum corrections to the kink mass, it simply reorganizes them.…”
Section: The Four Processesmentioning
confidence: 93%